The effect of operating conditions on heat transfer for parallel plate heat exchangers of thermoacoustic standing wave systems - Mohd Sa'at, Fatimah Al-Zahrah; Hamood Al-Masoodi, Ahmed Hasan; Jaworski, Artur J. (Elsevier B.V., 2024)
Thermoacoustic systems represent a promising technology for clean cooling and/or power generation. However, understanding of the behavior of oscillatory flow inside the system under high drive ratio operating conditions, at elevated mean pressures, range of frequencies, and high flow amplitudes, remains limited and poses challenges for designing efficient systems with minimal losses. This paper presents a numerical investigation into the flow and heat transfer characteristics across a coupled cold and hot parallel-plate heat exchanger operating under standing-wave type oscillatory flow conditions. The models were developed for various conditions, spanning frequencies from 13 Hz to 100 Hz and mean pressures between 1 and 20 bar, using both nitrogen and helium as working fluids. The study reveals significant phenomena such as heat accumulation and annular effects in both temperature and velocity/vorticity fields. These findings were discussed in the context of their impact on the heat transfer performance of the heat exchanger. Specifically, the emergence of vortices was examined in relation to mean pressure, alongside jet-like velocity profiles and natural convection effects. Furthermore, the paper includes a comparative analysis between the heat transfer model employed in this study and previous works, aiming to validate the findings. This research enhances the understanding of fluid dynamics and heat transfer phenomena within heat exchangers of thermoacoustic devices, thereby contributing to advancements in future design improvements.